Epidemiology of Sjögren Syndrome in Africa: A Scoping Review. - (:unkn) unknown (My University, 2021)
Background The epidemiology of Sjögren syndrome (SS) has been extensively studied in America, Europe, and Asia.Objective To summarize available data on the epidemiology of SS in Africa.Methods MEDLINE, EMBASE, and African Journals Online were searched from inception up to May 17, 2020, to identify relevant articles. Data gleaned from these reports have been summarized narratively in this review.Results Twenty-one hospital-based studies were included. These studies reported 744 cases of SS. The mean age at diagnosis varied between 28 and 73.6 years, and the female proportion ranged from 83.3% to 100%. There was no population-based incidence or prevalence. Among people with autoimmune and other rheumatic conditions, the frequency of primary SS was in the range 1.9% to 47.6%, whereas that of rheumatoid arthritis–associated secondary SS was in the range 4.3% to 100%. Sicca symptoms were the commonest features, with most frequently involved organs being joints, lungs, and neurological structures. Main autoantibodies were anti-Ro/SS antigen A, anti-La/SS antigen B, and antinuclear antibodies.Conclusions The epidemiology of SS is poorly characterized in Africa. Available data are broadly consistent with those from other populations. Extensive and high-quality research is urgently needed.
Keywords: African Research